The use of Hericium erinaceus and Trametes versicolor extracts in supportive treatment in oncology - Winder Mateusz; Bulska-Będkowska Weronika; Chudek Jerzy (Acta Pharmaceutica)
Substances available in nature with potential therapeutic effects are the subject of research that raises tremendous hopes for new challenges in medicine. Fungi are the most common organisms in the ecosystem and the most interesting in this respect. This review discusses two species of edible fungi, used for centuries in Eastern natural medicine, with the best-documented effect – Hericium erinaceus (He) and Trametes versicolor (Tv). The results of in vivo and in vitro studies conducted on mice and human cell lines demonstrate immunomodulatory, potentially, anticancer, anti-inflammatory and neuroregenerative effects of substances isolated from these fungi. The substances contained in the extracts of He and Tv seem to have immunomodulatory effects that may support chemotherapy. The use of these extracts is justified stronger than the other supportive treat ments based on supplements.